2021
DOI: 10.1016/j.cjco.2020.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Obstructive Sleep Apnea in an Atrial Fibrillation Population: What’s the Best Test?

Abstract: Background: Among individuals with nonvalvular atrial fibrillation (AF), the prevalence of obstructive sleep apnea (OSA) can be as high as 85%. Continuous positive airway pressure treatment for moderate or severe OSA might improve AF outcomes and quality of life, so early identification of OSA might be of value. However, screening questionnaires for OSA are suboptimal because they are weighted toward tiredness and loud snoring, which might be absent in AF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…As mentioned before, OSA is highly underdiagnosed in the AF population, despite a prevalence of up to 86% in AF patients recruited in a community cardiology clinic ( 14 ). Our study is in line with this finding, although our study patients had a higher pretest probability.…”
Section: Discussionmentioning
confidence: 96%
“…As mentioned before, OSA is highly underdiagnosed in the AF population, despite a prevalence of up to 86% in AF patients recruited in a community cardiology clinic ( 14 ). Our study is in line with this finding, although our study patients had a higher pretest probability.…”
Section: Discussionmentioning
confidence: 96%
“…This study is not the first to demonstrate the limited value of the STOP-Bang questionnaire as an SDB-screening tool in AF patients. Several studies reported its moderate to poor performance in detecting moderate-to-severe SDB in AF patients in different clinical settings [ 6 , 7 , 14 16 ]. The relatively high false negative rate and low sensitivity have been mentioned as factors limiting the usefulness of the STOP-Bang questionnaire [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Originally, the questionnaire was not developed specifically for AF patients. Due to interrelations between SDB and AF, the shared risk factor profile, and the fact that symptoms of SDB and AF are often overlapping, the STOP-Bang items might have limited predictive value [ 6 , 7 , 14 19 ]. Indeed, in our cohort, some overlapping characteristics could be revealed with correlation analysis of the STOP-Bang items, for example, between the item neck circumference and observed apnoea/snoring, high blood pressure or male gender.…”
Section: Discussionmentioning
confidence: 99%
“…These questionnaires will be a good starting point to identify patients with AF who have OSA but more objective test, such as the home sleep apnea testing, is encouraged for those with AF to rule out OSA. [77][78][79][80] Metoprolol has been shown to prevent AF in animal models with chronic OSA by inhibiting atrial structural, sympathetic nervous and metabolic remodeling 81,82 studies to demonstrate this effect in humans will be valuable. OSA has been associated with increased incidence of extra-PV triggers of AF, and elimination of these triggers reduces arrhythmia recurrence.…”
Section: The Relationship Of Therapy Of Osa and Afmentioning
confidence: 99%